KEBIJAKAN PENUNTUTAN BERBASIS KEADILAN RESTORATIF DI INDONESIA - Bayu Aji Adhyarsa (2022)
The completion of cases out of court using the concept of Restorative Justice is currently getting attention from the legal community. The principle of Restorative Justice is one of the methods of legal settlement that is considered effective by several groups, including the Indonesian Attorney General's Law Enforcement Institution. The Prosecutor's institution as the controller of the case process (dominus litis), has a central position in law enforcement, because only the Prosecutor's institution can determine whether a case can be submitted to the Court or not based on valid evidence according to the Criminal Procedure code. By using a juridical-normative research method that seeks to find out how the position of the Restorative Justice-based prosecution policy in the criminal justice system in Indonesia and how the implementation of Restorative Justice-based prosecution policy in the Prosecutor's instituition of the Republic of Indonesia. As a result, the position of termination of prosecution based on Restorative Justice by the Prosecutor's Office was initiated by a mutual agreement on October 17, 2012 between the Chief Justice of the Supreme Court of the Republic of Indonesia, the Minister of Law and Human Rights of the Republic of Indonesia, the Attorney General of the Republic of Indonesia and the Head of the Indonesian National Police which the Attorney General placed in the Strategic Plan of the Prosecutor's institution for 2020-2024 and Regulation of the Attorney General of the Republic of Indonesia Number 15 of 2020 concerning Termination of Prosecution Based on Restorative Justice and the application of a prosecution policy based on restorative justice is carried out by the Attorney General by delegating part of his "deponeering" authority to the Public Prosecutor in the form of "quasi seponeering". Key Words: Restorative Justice, Quasi Seponeering.